The Effect of Eat, Rest and Exercise Habits on Anemia in Adolescents - Saddiyah Rangkuti (Science Midwifery, 2019)
Effect of eating habits, rest and exercise on anemia in adolescents. Anemia is the most common nutritional problem, both in developed and developing countries, and in people with low and high socioeconomic status. Anemia can occur in anyone and in any age group. The purpose of this study was to determine the relationship between the eating habits of adolescent girls and the incidence of anemia in female high school students in Medan. This study aims to determine the relationship between female adolescent rest habits and the incidence of anemia in female high school students in Medan. The purpose of this study was to determine the relationship between female adolescent exercise habits and the incidence of anemia in female high school students in Medan. The study was conducted for two months starting from March to April 2019. From the multivariate analysis of modeling the incidence of anemia, there are three variables that have a significant relationship with the incidence of anemia, namely attitudes, eating habits and menstrual patterns.